Remote light-controlled intracellular target recognition by photochromic fluorescent glycoprobes - Zhang, Junji; Fu, Youxin; Han, Hai-Hao; Zang, Yi; Li, Jia; He, Xiao-Peng; Feringa, Ben L.; Tian, He (Nature communications, 2017)
Development of powerful fluorescence imaging probes and techniques sets the basis for the spatiotemporal tracking of cells at different physiological and pathological stages. While current imaging approaches rely on passive probe–analyte interactions, here we develop photochromic fluorescent glycoprobes capable of remote light-controlled intracellular target recognition. Conjugation between a fluorophore and spiropyran produces the photochromic probe, which is subsequently equipped with a glycoligand “antenna” to actively localize a target cell expressing a selective receptor. We demonstrate that the amphiphilic glycoprobes that form micelles in water can selectively enter the target cell to operate photochromic cycling as controlled by alternate UV/Vis irradiations. We further show that remote light conversion of the photochromic probe from one isomeric state to the other activates its reactivity toward a target intracellular analyte, producing locked fluorescence that is no longer photoisomerizable. We envision that this research may spur the use of photochromism for the development of bioimaging probes. Fluorescence sensing in biological environments is prone to background signal interference. Here the authors design a photochromic fluorescent glycoprobe for light-controlled photo-switchable cell imaging and photo-activated target recognition, resulting in an increased sensing precision.